If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b-(2-b)=(3/2)(b+12)
We move all terms to the left:
3b-(2-b)-((3/2)(b+12))=0
Domain of the equation: 2)(b+12))!=0We add all the numbers together, and all the variables
b∈R
3b-(-1b+2)-((+3/2)(b+12))=0
We get rid of parentheses
3b+1b-((+3/2)(b+12))-2=0
We multiply parentheses ..
-((+3b^2+3/2*12))+3b+1b-2=0
We multiply all the terms by the denominator
-((+3b^2+3+3b*2*12))+1b*2*12))-2*2*12))=0
We calculate terms in parentheses: -((+3b^2+3+3b*2*12)), so:Wy multiply elements
(+3b^2+3+3b*2*12)
We get rid of parentheses
3b^2+3b*2*12+3
Wy multiply elements
3b^2+72b*1+3
Wy multiply elements
3b^2+72b+3
Back to the equation:
-(3b^2+72b+3)
576b^3*1-(3b^2+72b+3)=0
We get rid of parentheses
576b^3*1-3b^2-72b-3=0
We do not support ebpression: b^3
| 6(3a+1)+4=100 | | 30+6p=7(p+6)5 | | 2/4x+4=22 | | 3(t+1)=1/2-5t | | 8.9-3.3j=2.1j+2.3 | | 0.333x=0.25x+2 | | 3n+2=10+5n | | 7t+4t=10+15-14 | | 7t-4t=10+15-14 | | 4a-7=-6a+19 | | 5-5=13x-6x | | 26x+136=180 | | 11m-13m=8 | | 5-41=4a | | 6-24=6a | | 6-14=6a | | 2r=-11+15 | | -19m+12=-14m-4 | | 2.65+x=4 | | 19.2+23.8x=-64.1 | | 5x-7-3x+16=-4x-11-8x+5 | | 3p-2p=-9+17 | | 3p-2p=9+17 | | 5.d+3.7=42 | | 1.4x=0.028 | | 5x-7-3x+16=-4-11-8x+5 | | 5+3.7.d=42 | | 5+3.7×d=42 | | 5+3.7=42.d | | 5+3.7=42×d | | (-41/4)z=-17 | | -1(q-29)=1/2(4-8q) |